Disorders of perception in tumors of the parietal lobe of the brain - Jerí, Raúl (1953)
Eleven case parietal brain tumors described location and especially the perceptual disturbances clinical analyzes. Histological examination revealed that it was three glioblastomas three tuberculomas two metastatic carcinomas, one oligodendroglioma, astrocytoma and meningioma. There was correlation between the hand and the extent of injury to, comparable to the findings of prior disclosures in cases of vascular and traumatic nature clinical manifestations. A review of the physiology and the semiology of the parietal lobes of the brain is done.